Towards a multi-source fusion approach for eye movement-driven recognition - Rigas, Ioannis; Abdulin, Evgeniy; Komogortsev, Oleg (Information fusion, 2016)
•We investigate the effects of multi-source fusion in the field of eye movement biometrics.•We introduce the concept of multi-stimulus fusion.•We suggest a weighted fusion scheme based on stimulus-specific and algorithm-specific weights.•The proposed weight-training procedure is based on the identification performance.•The results show a considerable improvement in performance for the field of eye movement biometrics. This paper presents a research for the use of multi-source information fusion in the field of eye movement biometrics. In the current state-of-the-art, there are different techniques developed to extract the physical and the behavioral biometric characteristics of the eye movements. In this work, we explore the effects from the multi-source fusion of the heterogeneous information extracted by different biometric algorithms under the presence of diverse visual stimuli. We propose a two-stage fusion approach with the employment of stimulus-specific and algorithm-specific weights for fusing the information from different matchers based on their identification efficacy. The experimental evaluation performed on a large database of 320 subjects reveals a considerable improvement in biometric recognition accuracy, with minimal equal error rate (EER) of 5.8%, and best case Rank-1 identification rate (Rank-1 IR) of 88.6%. It should be also emphasized that although the concept of multi-stimulus fusion is currently evaluated specifically for the eye movement biometrics, it can be adopted by other biometric modalities too, in cases when an exogenous stimulus affects the extraction of the biometric features.